2017
DOI: 10.1080/01416200.2017.1329706
|View full text |Cite
|
Sign up to set email alerts
|

‘These religions are no good – they’re nothing but idol worship’: mis/representation of religion in Religious Education at school in Malawi and Ghana

Abstract: This article draws data from two complementary studies in sub-Saharan Africa to highlight the problem of religious misrepresentation in (multi-faith) Religious Education (RE) at school in Malawi and Ghana. Employing Michael Apples' conception of selective tradition, the article is critical of the confrontational disputation inherent in the RE in the two countries. The misrepresentation is analysed under themes related to classroom discourse and the nature of religion. It argues that RE could actually be counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Although curriculum cannot eradicate religious abuse completely, I argue that the https://theologiaviatorum.org Open Access curriculum, as an embodiment of social solutions to human ambivalence, such as religious abuse, has the capacity to emancipate students and educators, so that they become confident about confronting, challenging and evoking epistemic disobedience against religious abuse. Thus, with the lens of CER, I agree with Matemba and Addi-Mununkum (2017) that:…”
Section: Rethinking Religious Education In Zimbabwe: Evoking a Relevant Curriculum For Family And Religious Studiessupporting
confidence: 60%
“…Although curriculum cannot eradicate religious abuse completely, I argue that the https://theologiaviatorum.org Open Access curriculum, as an embodiment of social solutions to human ambivalence, such as religious abuse, has the capacity to emancipate students and educators, so that they become confident about confronting, challenging and evoking epistemic disobedience against religious abuse. Thus, with the lens of CER, I agree with Matemba and Addi-Mununkum (2017) that:…”
Section: Rethinking Religious Education In Zimbabwe: Evoking a Relevant Curriculum For Family And Religious Studiessupporting
confidence: 60%
“…The contentious reforms and the historical periods within which they were carried out in Malawi have been studied, and clearly demonstrate religious tensions, ideological differences, and political wrangling of the various stakeholders involved. Over the years, the provision of RE has had some alternations as discussed below (Matemba and Addai-Mununkum, 2019). An article by Matemba found that since missionary times, a predominantly Bible-based curriculum has been offered in Malawi schools in RME.…”
Section: Religious Education: Provision Reforms and Issuesmentioning
confidence: 99%
“…However, bringing about changes to deep-rooted values and beliefs is problematic. This has the risk of protests from powerful Christian lobby groups, and also requires resources for upskilling teachers and teacher trainers (Matemba and Addai-Mununkum, 2019). It was also argued that multi faith RME would not easily be accepted in a homogeneous country like Malawi, where Christianity is the dominant religion.…”
Section: Religious Education: Provision Reforms and Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…High school-age students seem to be influenced by the idea that modern science has refuted religious truth-claims (Walker 2019). Matemba and Addai-Mununkum (2019), in their study of schools in Malawi and Ghana, claim that Religious Education could even turn out to be counter-productive, resulting in the misrepresentation, rather than the promotion, of religions; particularly in those areas where a religion, such as Islam, has been hijacked by extremist groups with tragic consequences. This is the case of the recent terrorism activities perpetrated by ISIS in Europe, Al-Shabbab in in Kenya and Somalia, or Boko Haram in Nigeria.…”
Section: Introductionmentioning
confidence: 99%